A new carbazole-based colorimetric and fluorescent sensor with aggregation induced emission for detection of cyanide anion. (May 2019) - Zou, Qiqi; Tao, Furong; Wu, Hongtao; Yu, William W.; Li, Tianduo; Cui, Yuezhi
Abstract: A new carbazole-based naked-eye colorimetric and fluorescent sensorCPPB with aggregation induced emission (AIE) effect was successfully synthesized. The solid powder ofCPPB emitted intense yellow fluorescence, and its emission wavelength and fluorescence intensity in DMSO/H2 O solution varied with the percentage of water ( f w ). Nano-aggregates ofCPPB molecules were prepared by increasing f w of DMSO/H2 O solution, and the optimal aggregation state ofCPPB was reached in 99% aqueous DMSO solution with the maximum fluorescence intensity. Moreover, CPPB displayed high selectivity and sensitivity toward cyanide anions (CN − ) in 99% aqueous DMSO solution even in the presence of other competitive anions (CN −, F −, Cl −, AcO −, NO3 −, I −, CO3 2−, HCO3 −, HSO3 −, SO4 2−, S 2−, HS −, OH −, H2 PO4 − and HPO4 2− ) and the reactive oxygen species (H2 O2, O2 ·−, 1 O2, t-BuOOH and ·OH). The sensing mechanism for CN − was confirmed by optical spectral studies, 1 H NMR titration, HRMS spectra, Job's plot analyses and DFT calculations. SensorCPPB for CN − detection revealed extremely low detection limit (67.4 nM), high anti–interference ability, wide pH response range (3.0–10.0) as well as the immediate response (15 s). Furthermore, theCPPB -based test strips were applied to detect CN − qualitatively and quantitatively in 100% aqueous solution. Graphical abstract: We have successfully developed sensor CPPB, which exhibited distinct aggregation induced emission (AIE) effect, and detected CN− based on naked-eye colorimetric and fluorescent sensing with high selectivity and great sensitivity.Image 1 Highlights: Carbazole-based sensor CPPB was designed and synthesized, which exhibited obvious aggregation induced emission (AIE) effect. Sensor CPPB detected CN − in 99% aqueous DMSO solution, and the test strips of CPPB recognized CN − in 100% aqueous solution. The detection limit of CPPB for CN − were at nanomolar level in 99% aqueous DMSO solution. Colorimetric responses of CPPB toward CN − were visible with the naked eyes under sunlight and UV lamp (365 nm).